HUBUNGAN POLA ASUH ORANG TUA DENGAN TOILET TRAINING PADA ANAK USIA 3-5 TAHUN DI JOMBANG - Putri, Grahita Widya; Sasmito, Nanang Bagus; Aziz, Aditya Nur Aminudin (LPPM STIKes Bahrul Ulum Jombang, 2020)
At preschool age, the ability of the urethral sphincter and the anal sphincter is ready. The readiness of toilet training in children is not only influenced by physical, psychological, mental and parenting practices. There are three types of parenting among them authoritarian, permissive, and democratic. The purpose of this study was to determine the relationship of Parenting Parents with Toilet Training in Children Aged 3-5 Years in PAUD KB AL-Firdaus Bahrul Ulum Tambakberas Jombang. This research uses correlation analytic design with a cross-sectional approach. The sample used was 42 respondents. The sampling technique used is a total sampling. Data collection using a questionnaire. The pattern of parenting in toilet training that experienced delays of almost half had permissive parenting as many as 15 children (35.7%). Data analysis was performed using the Chi-Square test. Based on the statistical test, there is a relationship between Parenting Parents and Toilet Training in Children Aged 3-5 Years in PAUD KB AL-Firdaus Bahrul Ulum Tambakberas Jombang with p-value (0.012) <(α: 0.05). Parents who apply parenting by the character of the child and according to the situation will make the child develops better in doing urinating (BAK) and defecating (BAB) independently.